Hankel Determinants of Normalized Analytic Functions Associated with Hyperbolic Secant Function - Kumar, Sushil; Breaz, Daniel; Cotirla, Luminita-Ioana; ÇETİNKAYA, ASENA (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In this paper, we consider a subclass of normalized analytic functions associated with the hyperbolic secant function. We compute the sharp bounds on third- and fourth-order Hermitian–Toeplitz determinants for functions in this class. Moreover, we determine the bounds on second- and third-order Hankel determinants, as well as on the generalized Zalcman conjecture. We examine a Briot–Bouquet-type differential subordination involving the Bernardi integral operator. Finally, we obtain a univalent solution to the Briot–Bouquet differential equation, and discuss the majorization property for such function classes. © 2024 by the authors.
Keywords: Briot–bouquet Differential Subordination; Hermitian–toeplitz and Hankel Determinants; Hyperbolic Secant Function; Majorization; Starlike Functions